AI and HR: Exploring Data-Driven Solutions for Optimizing Human Resource Practices - Padma, Satuluri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research seeks to explore the impact of Artificial Intelligence (AI) on Human Resource Management (HRM), with a particular focus on key areas such as recruitment, selection, and employee performance management. The study aims to identify effective AI tools that can be integrated into HR practices, thereby enhancing the efficiency and effectiveness of these processes. By examining how AI can streamline recruitment and selection, the research will offer insights into improving talent acquisition and ensuring better candidate-job fit. Moreover, the study will delve into AI's role in employee performance management, assessing how data-driven insights can optimize performance evaluations, goal setting, and employee development. Through a comprehensive analysis, the research will also address the long-term effects of integrating AI into HRM, particularly in relation to potential challenges and restrictions. The ultimate goal of this research is to provide a roadmap for leveraging AI to improve HR processes and management practices. By understanding the benefits and limitations of AI in HR, organizations can make informed decisions about adopting AI technologies, leading to more effective HR strategies and enhanced overall organizational performance.